The MECE Muse - Lindor, Christie (Ascent Audio, 2018)
Great consultants possess a je ne sais quoi that are equal parts confidence, passion, technical acumen, purpose, and charisma. Great consultants are authentically imperfect; they take life by the reins and forge ahead with certainty no matter how complex a situation is, in an almost effortless way. Great consultants are humble yet make everyone around them step their game up. Great consultants take care of their people. Clients thank good consultants; clients are wowed by great consultants. Management consultant Christie Lindor has quietly been on a mission to be the mentor she wishes she had earlier in her consulting career. With fifteen years of experience working at top management consulting firms, Christie is now sharing secrets of great consultants in this new consulting business book. Christie conducted research by connecting with over fifty top consulting partners across twenty seven consulting organizations on what makes a great consultant, including thought leadership from eight out of the top ten consulting firms in the world. The MECE Muse is an insider's guide to consulting, providing invaluable insights and practical knowledge including unwritten rules, career strategies, in addition to interviews from top industry consulting leaders who relate their personal experiences and offer unique perspectives on building and maintaining a successful consulting career.